The Importance Factors That Students Consider in Choosing a University - Dedy Ansari Harahap; Dita Amanah; Muji Gunarto; Purwanto Purwanto (Migration Letters, 2023)
The purpose of this paper is to analyze the effect of university image and quality of lecturers on student decisions to choose a university. To achieve the proposed goals, a model is applied that reflects the effect of university image and quality of lecturers on student decisions to choose universities. This model was tested through the use of multiple linear regression equations and the sample was 388 student candidates. The results show that the image of the university and the quality of the lecturers have an influence on student decisions to choose a campus. The conceptual model shows that the image of a university is the most influential construct on student decisions to choose a campus, followed by the quality of lecturers. This implies that in the future higher education leaders pay more attention to the image of the university and the quality of lecturers that can build public trust and prospective students determine the choice of place to continue their studies.In this paper, the university image of 0.918 and a lecturer quality of 0.937. Further research is needed in order to find more reliable measurements of indicators of university image and quality of lecturers.